The crystal packing and slip plane analysis in mechanical properties improvement of mefenamic acid by cocrystallization with nicotinamide coformer - Ari Wahyudi; Utami, Dwi; Setianto , Arif Budi (Communications in Science and Technology, 2020)
Mefenamic acid is an analgesic non-steroidal anti-inflammatory drug (NSAID) that is categorized as Biopharmaceutical Classification System (BCS) class II drug. Cocrystallization of mefenamic acid (MFA) with nicotinamide (NIC) has been reported to enhance the solubility of MFA for about 2.56 times higher than pure MFA. As a part of MFA-NIC development in pharmaceutical dosage form, we reported the improvement of mechanical properties of MFA-NIC cocrystal based on the presence of slip planes in crystal structure. The research was initially by synthesizing and characterizing the cocrystal by using X-ray diffraction analysis, and was followed by the investigation of the mechanical properties of MFA and its cocrystal, i.e. tensile strength and deformation parameter. The correlation of crystal structure with mechanical properties was determined by crystal packing motif and slip plane analysis from single crystal data by using Mercury 3.6. The tensile strength of MFA was acceptance at 20.0 MPa, and dropped at more than 25.0 MPa. A better tableting performance was observed in MFA-NIC cocrystal which had the tensile strength 1.5 times higher than MFA at 12.5 MPa and gradually increased with an increasing pressure up to 2.5 times at 22.5 MPa. The flat slip plane of MFA-NIC cocrystal was predicted as the key factor in the improvement of its mechanical properties, compared to zigzag slip plane of MFA. In conclusion, MFA-NIC cocrystal had the better mechanical properties than pure MFA due to its flat slip plane and it becomes potential to be explored in further development of solid dosage form.